2001
DOI: 10.1086/322040
|View full text |Cite
|
Sign up to set email alerts
|

The Etiology of Community‐Acquired Pneumonia at an Urban Public Hospital: Influence of Human Immunodeficiency Virus Infection and Initial Severity of Illness

Abstract: In a prospective study, the etiology of community-acquired pneumonia (CAP) was investigated among consecutive patients admitted to an academic, urban public hospital in Seattle. The study population was uniquely young, was predominantly male, and had high rates of homelessness, cigarette smoking, alcoholism, injection drug use, and human immunodeficiency virus (HIV) infection. Leading causes of CAP among HIV-negative patients were aspiration, followed by Streptococcus pneumoniae, Legionella species, and Mycopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 53 publications
8
68
0
7
Order By: Relevance
“…(14,15) The percentage found in this study sample is in accordance with the variation shown in other studies. (1)(2)(3)(4)(5)(6)(16)(17)(18)(19) The infection typically affects elderly individuals with preexisting chronic pathologies such as COPD, cardiovascular diseases, alcoholism and diabetes mellitus, as well as hemodialysis patients with chronic kidney disease. (2,4,6) Young or previously healthy individuals can also be affected, principally when they present predisposing factors such as skin infections (impetigo, abscess, cellulitis, furunculosis or infected wound) or infections of the genital tract associated with septic abortion, all of which represent hematogenous dissemination of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…(14,15) The percentage found in this study sample is in accordance with the variation shown in other studies. (1)(2)(3)(4)(5)(6)(16)(17)(18)(19) The infection typically affects elderly individuals with preexisting chronic pathologies such as COPD, cardiovascular diseases, alcoholism and diabetes mellitus, as well as hemodialysis patients with chronic kidney disease. (2,4,6) Young or previously healthy individuals can also be affected, principally when they present predisposing factors such as skin infections (impetigo, abscess, cellulitis, furunculosis or infected wound) or infections of the genital tract associated with septic abortion, all of which represent hematogenous dissemination of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Самой частой этиологической причиной ВП у боль ных ВИЧ инфекцией является Streptococcus pneumo niae, реже -Haemophilus influenzae [25][26][27][28][29][30].…”
Section: этиология вп у лжвunclassified
“…Замечено, что у больных ВИЧ инфек цией чаще, чем в общей популяции регистрируются MRSA штаммы S. aureus, особенно при низком со держании CD4 клеток [31,32] Pseudomonas aerugi nosa также значительно чаще, чем у лиц без ВИЧ, выступает патогеном тяжелой ВП. В свою очередь, роль таких атипичных возбудителей, как Legionella pneumophila, Mycoplasma pneumoniae и Chlamydophi la pneumoniae значительно скромнее в этиологии ВП у больных ВИЧ инфекцией, чем у лиц без ВИЧ [27][28][29][30][31].…”
Section: этиология вп у лжвunclassified
“…1,2 Its incidence has decreased after the introduction of highly active antiretroviral therapy (HAART); 3,4 however, these patients still have a higher risk of acquiring this type of infection, when compared to the general population, 3 in addition to having higher rates of invasive pneumococcal disease 5 and mortality. 6,7 The etiology of community-acquired pneumonia (CAP) in HIV-infected patients is similar to that of immunocompetent patients, with the main agent being Streptococcus pneumoniae. Infections by Gram-negative bacteria (including Haemophilus influenzae, Pseudomonas aeruginosa and Legionella pneumophila, among others) are common, as well as by Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
“…Infections by Gram-negative bacteria (including Haemophilus influenzae, Pseudomonas aeruginosa and Legionella pneumophila, among others) are common, as well as by Staphylococcus aureus. 1,2,3,6 The following are considered risk factors for CAP in HIV-infected patients: low socioeconomic level, smoking, alcohol consumption, use of intravenous (IV) drugs, comorbidities (including cardiovascular disease, kidney disease or liver cirrhosis), malnutrition, low CD4+ T-cell counts (CD4 < 200 cells/µL), HIV replication and lack of HAART. 2 Regarding prevention, the role of the antipneumococcal vaccine in HIV-infected patients is yet to be defined, as the studies have shown controversial results.…”
Section: Introductionmentioning
confidence: 99%